Assessing children’s language development: a systematic literature review on early language milestone scales - Khazriyati Salehuddin,; Fatin Nadiah Mahmud, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Early language milestone (ELM) scales are used to assess language development in young children, especially for early detection of atypical language development. However, not all ELM scales are layperson-friendly and are suitable for all language acquirers. Therefore, this article presents a systematic literature review (SLR) of the existing ELM scales. This SLR used the PICo approach to select and review past studies ranging from 2013 to 2023, investigating the language(s), the target groups, and the constructs and items of existing ELM scales. Past studies on ELM scales were identified via the PRISMA approach from four online databases, namely, Scopus, PubMed, Web of Science, and Science Direct. From a total of 892 studies, only 19 studies were systematically reviewed; they cover ELM scales in 18 languages and language varieties which have been proven to be reliable and valid. Generally, the results show that the existing ELM scales can be used to assess children’s language development in terms of receptive and expressive language skills from an early age. The findings show that the ELM scales were primarily developed to gauge the language development of children acquiring English as their first and/or second language; however, no ELM scale has been developed to meet the needs of children acquiring English and Malay as their first languages in the Malaysian context. This SLR directs future research on developing an ELM scale for Malay-English bilingual first language acquirers.